Effect of Multistage Thermal Cracking on Permeability of Granite - Zi-jun Feng; Yang-sheng Zhao; Peng Zhao; Zhi-jun Wan (Advances in Materials Science and Engineering)
Experiments on thermal cracking in granite sample were conducted through acoustic emission monitoring, and changes in permeability were concomitantly studied using 600°C 20 MN servo-controlled triaxial rock mechanics testing machine. Two granite samples, 200 mm in diameter and 400 mm long, from Shandong, China, were selected for these experiments. Both samples were heated up to 500°C at ambient pressure. We find that thermal cracking of large-scaled granite is discontinuous and exhibits multiple stages with temperature. In addition, the permeability exhibits the following characteristics: (a) it neither increases nor decreases monotonously with the temperature rising and it exhibits multipeak due to the multistage thermal cracking; (b) the temperature of permeability peak lags behind that of the drastic acoustic emission activities. Both AE counts and permeability dramatically increased after 300°C, which indicated serious thermal cracking occurred after 300°C. Permeability ratio is approximately linear with the ratio of AE cumulative counts. The results will be helpful for understanding the mechanism of geothermal reservoir construction and long-term evaluation of safety for nuclear waste geological disposal.